2017
DOI: 10.1007/s00253-017-8089-8
|View full text |Cite|
|
Sign up to set email alerts
|

Optimized synthesis of novel prenyl ferulate performed by feruloyl esterases from Myceliophthora thermophila in microemulsions

Abstract: Five feruloyl esterases (FAEs; EC 3.1.1.73), FaeA1, FaeA2, FaeB1, and FaeB2 from Myceliophthora thermophila C1 and MtFae1a from M. thermophila ATCC 42464, were tested for their ability to catalyze the transesterification of vinyl ferulate (VFA) with prenol in detergentless microemulsions. Reaction conditions were optimized investigating parameters such as the medium composition, the substrate concentration, the enzyme load, the pH, the temperature, and agitation. FaeB2 offered the highest transesterification y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Selectivity was >1 (meaning that transesterification is higher than hydrolysis) only for Fae125, C1FaeB1 and C1FaeB2 for both products. In a previous work, PFA was synthesized by SF5 and 6 FAEs from M. thermophila C1, confirming that SF6 FAEs have higher specificity and increased yield, rate, and selectivity during transesterification with prenol than SF5 FAEs [11]. BFA has been synthesized by immobilized or free commercial enzymatic preparations, AnFaeA from A. niger, and StFaeC from Sporotrichum thermophile (syn.…”
Section: Synthesis Of Aliphatic Estersmentioning
confidence: 59%
See 1 more Smart Citation
“…Selectivity was >1 (meaning that transesterification is higher than hydrolysis) only for Fae125, C1FaeB1 and C1FaeB2 for both products. In a previous work, PFA was synthesized by SF5 and 6 FAEs from M. thermophila C1, confirming that SF6 FAEs have higher specificity and increased yield, rate, and selectivity during transesterification with prenol than SF5 FAEs [11]. BFA has been synthesized by immobilized or free commercial enzymatic preparations, AnFaeA from A. niger, and StFaeC from Sporotrichum thermophile (syn.…”
Section: Synthesis Of Aliphatic Estersmentioning
confidence: 59%
“…During the last 16 years, FAEs have gained increased attention as tools for the synthesis of novel hydroxycinnamates with enhanced anti-oxidant activity and tailor-made lipophilicity with potential applications in the food, pharmaceutical, and cosmetics industries [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The increased stability in organic solvents is one of the most important advantages of CLEAs in various synthetic applications. Feruloyl esterases have been used extensively in the literature for various (trans)esterifications [4,32] and in non-conventional systems, and thus, a certain degree of stability in non-aqueous media is necessary. In the present study, the stability in organic solvents was found to be comparable to the respective soluble FAEs.…”
Section: Discussionmentioning
confidence: 99%
“…It is biosynthesized from shikimate pathway via phenylalanine or Ltyrosine 1 . In nature, FA is usually found as component of plant cell walls offering linkage with lignin; in arabinoxylans, FA is esterified to the C-5 of αlarabinofuranose; in pectins, it is esterified to the C-2 of α1➔5-linked arabinofuranose or to the C-6 of β1➔4-linked galactopyranose, while in xyloglucans, it is found attached to the C-4 of α-D-xylopyranose 2,3 . FA exhibits a wide range of therapeutic effects against various diseases such as cancer, diabetes, and cardiovascular and neurodegenerative disorders 4 .…”
Section: Introductionmentioning
confidence: 99%
“…An intermediate vinyl ferulate was first chemically produced by the enzymatic synthesis and subsequently esterified with phytosterols through alcoholysis with Candida rugosa as a catalyst 6 . Similarly, an optimized synthesis of novel prenyl ferulate was performed by feruloyl esterases from Myceliophthora thermophila in microemulsions 3 . A solvent-free and reduced pressure evaporation system was developed for lipase-catalyzed synthesis of 2-ethylhexyl ferulate from FA and 2-ethylhexanol 11 .…”
Section: Introductionmentioning
confidence: 99%